1993
DOI: 10.1073/pnas.90.13.5881
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and biology of natural and designed enediynes.

Abstract: Ever since the initial re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
172
0
4

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(177 citation statements)
references
References 50 publications
1
172
0
4
Order By: Relevance
“…13 Similar to the conventionally used cytotoxic agent daunorubicin, calicheamicin is an anthracyclin that probably acts by binding to the minor groove of DNA and introduction of double-strand DNA breaks. 14,15 Multicenter phase II trials have shown a 30% overall response rate in relapsed AML patients. 16,17 Surprisingly, similar to the results obtained by others, 18 in the cohort of AML patients treated with GO in our institute, we observed no clear correlation between the CD33 expression on the leukemic blasts and the response to therapy (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…13 Similar to the conventionally used cytotoxic agent daunorubicin, calicheamicin is an anthracyclin that probably acts by binding to the minor groove of DNA and introduction of double-strand DNA breaks. 14,15 Multicenter phase II trials have shown a 30% overall response rate in relapsed AML patients. 16,17 Surprisingly, similar to the results obtained by others, 18 in the cohort of AML patients treated with GO in our institute, we observed no clear correlation between the CD33 expression on the leukemic blasts and the response to therapy (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, nearly twenty of these natural enediynes have been identified, including calichemicin ␥ 1 I [6,7], dynemicin [8], and the esperamicins [9,10]. While these enediynes offer extremely high cytotoxic activities, their clinical use as anti-tumor agents has been limited due to their delayed activities and general toxicity [2][3][4][5].To overcome the shortcomings of these natural enediynes, a range of synthetic analogs have been explored [3,11], each with the goal of improved properties for clinical use. While still capable of cleaving DNA like the natural products through cycloaromatization reactions and subsequent hydride abstraction by the diradical intermediate [2-4, 11, 12], these analogs offer potential advantages, such as more controlled activation of the compound in vivo [13][14][15][16][17][18][19][20][21][22][23] or increased selectivity for tumor cells [24 -30].…”
mentioning
confidence: 99%
“…To overcome the shortcomings of these natural enediynes, a range of synthetic analogs have been explored [3,11], each with the goal of improved properties for clinical use. While still capable of cleaving DNA like the natural products through cycloaromatization reactions and subsequent hydride abstraction by the diradical intermediate [2-4, 11, 12], these analogs offer potential advantages, such as more controlled activation of the compound in vivo [13][14][15][16][17][18][19][20][21][22][23] or increased selectivity for tumor cells [24 -30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A), representative of a class of enediyne glycoconjugate DNA ligands, binds to and cleaves DNA at specific 4-bp sequences. Double-strand DNA cleavage occurs through bioreduction of the trisulfide and subsequent 1,4-benzenoid diradical formation, which results in hydrogen abstraction from adjacent nucleotide bases (10)(11)(12)(13). Affinity cleavage experiments (7,8) demonstrate that CLM preferentially cleaves DNA at cytosine-containing homopyrimidine tracts, preferentially TCCT.…”
mentioning
confidence: 99%